A community based study on finding the Quality of Life of the patients with Vitiligo - Dilshad Ahmad (Journal of Applied Pharmaceutical Science, 2017)
Vitiligo is a skin related disease and caused by the loss of skin color in blotches. It is a worldwide problem. By the treatment of vitiligo has improve the appearance of the affected skin of a person but there is no permanent cure treatment available for this disease. Data were collected from the individuals with Vitiligo who were under treatment in Dermatology clinic and were included in this study. A total of 200 individuals agreed to participate. Data were collected in the year of 2014 through a well-defined questionnaires and clinical examinations. We have carried out a detailed psychological analyses based on the response to queries. Patients with vitiligo averaged age was 32.4 ± 13.9 years. The maximum disability of the affected persons were measured by the DLQI summary score. Disability in patients was highest in treatment category with 54.71% of impairment followed by symptoms and feelings, with 41.48%. The present study has revealed that the association of Vitiligo with impairment in different aspects of life. Finally, the study showed that in the vitiligo patients’ quality of life are poor and it is directly associated with their social life. So, the quality of life to be improve is becoming a difficult task. From this study we understood the importance of DLQI sheet in designing and evaluation of efficacy of treatment on Vitiligo patients.
Keywords: Vitiligo,mental stigma,Quality of life,DLQI,Unani Medicine.